KETERSERAPAN ALUMNI MAHASISWA STKIP MUHAMMADIYAH PRINGSEWU LAMPUNG DALAM DUNIA PENDIDIKAN - Hendrowati, Triyuni; Istiani, Ana (Bappeda Kabupaten Pringsewu, 2018)
The purpose of this research is 1) to know the absorption of graduate student of STKIP Muhammadiyah Pringsewu Lampung in Schools in Pringsewu Regency, 2) Feedback from Government of Pringsewu Regency to increase quality of STKIP Muhammadiyah Pringsewu Lampung. The method used in this research is survey. The result of this research is 121 alumni of Counseling Guidance Study Program, 56 Alumni of Mathematics Study Program, 72 alumni of Indonesian Language and Literature Program, 87 alumni of English Education Study Program which is absorbed in Junior High Schools in Pringsewu District.